Does listed real estate behave like direct real estate? Updated and broader evidence - Hoesli Martin; Oikarinen Elias (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This study investigates a question relevant to many investors: do the broad Real Estate Investment Trust (REIT) return characteristics reflect those of the broad direct real estate markets. The paper makes several contributions to the literature in addition to using more recent data: (1) we use data for six countries (Australia, France, Germany, Netherlands, the U.K., and the U.S.); (2) we estimate both country-specific and panel models to increase the reliability and generalizability of the analysis; (3) we estimate a structural vector autoregressive model to be able to better and more reliably interpret the various shocks in the system; and (4) we investigate the effects of global liquidity shocks, among other shocks. Our results indicate that over the mid to long horizon, broad REIT and direct returns have similar characteristics and are highly correlated at the panel level. Also, the two types of exposure to real estate exhibit similar reactions to economic shocks. Thus, the paper makes a case that investors do not necessarily need to worry much about compositional effects when aiming to track broad international direct market performance by investing in listed real estate.